2018
DOI: 10.2147/ijgm.s178672
|View full text |Cite
|
Sign up to set email alerts
|

What factors influence the use of electronic health records during the first 10 minutes of the clinical encounter?

Abstract: PurposeThe use of electronic health records (EHRs) by physicians during the consultation is common and can be problematic. Factors influencing the use of EHRs during clinical encounters include physician and patient characteristics, consultation type as well as spatial organization of the room and type of EHR template. Their relative importance is however not well known. This study aimed to explore to what extent several physician, patient and consultation factors were associated with EHR use during the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…These variables were chosen because of their potential impact on EHR use preference. 21,42,43 We also recorded study location (hospital versus community emergency service) in order to account for potential location-related biases.…”
Section: Outcomes and Other Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…These variables were chosen because of their potential impact on EHR use preference. 21,42,43 We also recorded study location (hospital versus community emergency service) in order to account for potential location-related biases.…”
Section: Outcomes and Other Measuresmentioning
confidence: 99%
“…They include physicians' typing and computer skills, clinical experience, personal style of EHR use (particularly verbal and non-verbal behaviors), spatial arrangement of both the computer and the screen, and finally the design of the EHR. [17][18][19][20][21] Based on these observations, authors and experts in medical communication issued recommendations in order to facilitate patient-physician communication while using EHR during the encounter (see Box 1) 12,22,23 . These recommendations, based on principles of patient-centered approach, take into account physicians' verbal and non-verbal communication skills described in most physician-patient communication frames of reference 24,25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chan et al [35] found that doctors spent 50% less time using computers in examinations with psychological components than in examinations with no psychological components. Lanier et al [36] found that consultation content, physicians' gender and level of experience, and whether the consultation was new or a follow-up were modestly related to the way physicians used the computer in primary care settings.…”
Section: Doctor-patient-computer Interactionsmentioning
confidence: 99%
“…Researchers studying doctor-patient-computer interactions need to identify which interactions are taking place during the consultations. To do so, researchers have used qualitative methods such as taking notes during live observations [31,37], conducting interviews [37,38], administering questionnaires [39], and sending unannounced standardized patients to collect information [40] and quantitative methods such as videotaping consultations and manually coding the videos [36,41,42] or setting up complex mechanisms for automatic data collection and analysis inside the clinics [43]. Methods that include direct observations are likely to generate more accurate data than clinician or patient reports; however, direct observations are costly in terms of time and human resources, may be obtrusive in a clinical environment, and may cause the participants to knowingly or unknowingly alter their behavior (because of the presence of an observer) [44].…”
Section: Computational Ethnography Inside Clinicsmentioning
confidence: 99%